The ERRα–VDR axis promotes calcitriol degradation and estrogen signaling in breast cancer cells, while VDR‐CYP24A1‐ERRα overexpression correlates with poor prognosis in patients with basal‐like breast cancer. Issue 4 (16th July 2021) - Danza, Katia; Porcelli, Letizia; De Summa, Simona; Di Fonte, Roberta; Pilato, Brunella; Lacalamita, Rosanna; Serratì, Simona; Azzariti, Amalia; Tommasi, Stefania
Abstract : Vitamin D is used to reduce cancer risk and improve the outcome of cancer patients, but the vitamin D receptor (VDR; also known as the calcitriol receptor) pathway needs to be functionally intact to ensure the biological effects of circulating calcitriol, the active form of vitamin D. Besides estrogen receptor alpha (ERα), estrogen‐related receptor alpha (ERRα) has also been shown to interfere with the VDR pathway, but its role in the antitumor and transactivation activity of calcitriol is completely unknown in breast cancer (BC). We observed that ERRα functionally supported the proliferation of BC cell lines and acted as a calcitriol‐induced regulator of VDR. As such, ERRα deregulated the calcitriol–VDR transcription by enhancing the expression of CYP24A1 as well as of both ERα and aromatase (CYP19A1) in calcitriol‐treated cells. ERRα knockdown limited the effect of calcitriol by reducing calcitriol‐induced G0/G1 phase cell cycle arrest and by affecting the expression of cyclin D1 and p21/Waf. The interactome analysis suggested that Peroxisome Proliferator‐Activated Receptor Gamma Coactivator 1‐α (PGC‐1α) and Proline‐, glutamic acid‐, and leucine‐rich protein 1 (PELP1) are key players in the genomic actions of the calcitriol–VDR–ERRα axis. Evaluation of patient outcomes in The Cancer Genome Atlas (TCGA) dataset showed the translational significance of the biological effects of the VDR–ERRα axis, highlighting that VDR, CYP24A1, and ERRα overexpression correlates with poor prognosis in basal‐like BC. Abstract : Our study investigates the molecular effects elicited by the vitamin D derivative calcitriol in patients with breast cancer (BC). We showed that ERRα deregulated calcitriol/VDR‐dependent transcription, causing estrogen pathway activation and upregulation of the calcitriol degradation enzyme CYP24A1. We identified the ERRα/VDR‐interacting proteins by bioinformatics analysis and further demonstrated that simultaneous overexpression of VDR, CYP24A1, and ERRα correlated with poor prognosis in patients with basal‐like BC.